2001
DOI: 10.1159/000046731
|View full text |Cite
|
Sign up to set email alerts
|

Fat Absorption and Metabolism in Bile Duct Ligated Rats

Abstract: Background: Bile excretion is obstructed in children with extrahepatic bile duct atresia (EHBA) resulting in fat malabsorption and disturbed lipid metabolism. Aim: Investigate if the bile duct ligated rat exhibits similar deviations as patients with EHBA under different feeding conditions. Methods: 6 bile duct ligated Wistar rats and 12 matched paired controls were randomised over 3 feeding groups. Rats were killed 16 or 30 days postsurgery. Faeces, blood and livers were collected. Fat absorption was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…In support of this hypothesis, it has been shown that Cd causes a rapid decrease in bile flow and complete cholestasis in isolated perfused rat livers (Soto et al 2002). Moreover, cholestasis, by reducing bile flow, triggers malabsorption of dietary retinoids (de Vriese et al 2001;Weiss et al 2010). Several studies in rats have shown that dietary retinol associated with chylomicrons is, under normal conditions, taken up by hepatocytes, metabolized into retinaldehyde and retinoic acid by cytosolic alcohol dehydrogenases, retinol dehydrogenases and several aldehyde dehydrogenases before being accumulated, mainly in hepatic stellate cells (Parés et al 2008).…”
Section: Retinol and Biliary Acid Metabolismmentioning
confidence: 93%
See 1 more Smart Citation
“…In support of this hypothesis, it has been shown that Cd causes a rapid decrease in bile flow and complete cholestasis in isolated perfused rat livers (Soto et al 2002). Moreover, cholestasis, by reducing bile flow, triggers malabsorption of dietary retinoids (de Vriese et al 2001;Weiss et al 2010). Several studies in rats have shown that dietary retinol associated with chylomicrons is, under normal conditions, taken up by hepatocytes, metabolized into retinaldehyde and retinoic acid by cytosolic alcohol dehydrogenases, retinol dehydrogenases and several aldehyde dehydrogenases before being accumulated, mainly in hepatic stellate cells (Parés et al 2008).…”
Section: Retinol and Biliary Acid Metabolismmentioning
confidence: 93%
“…Indeed, absorption of dietary lipids requires the presence of BAs. Reduction in bile flow during cholestasis or after bile duct ligation triggers malabsorption of dietary fatty acids (de Vriese et al 2001). Moreover, it is well established that dietary fatty acids regulate the transcription levels of various genes involved in energy metabolism by activating several families of ligand-activated transcription factors such as the peroxysome proliferator-activated receptor (PPAR; Desvergne and Gerald 2007;Jump et al 2005;Schoonjans et al 1995).…”
Section: Energy Metabolismmentioning
confidence: 99%
“…De Vriese and colleagues reported the results of lipid analysis of BDL rats and identified hypercholesterolemia and changes in the serum phospholipid profile, in proportion to serum levels of total bilirubin and ALP; however, a decrease in liver fat content in BDL rats was also observed [4]. In a more recent study, a high-cholesterol diet was not found to cause hepatic steatosis in BDL mice [25].…”
Section: Discussionmentioning
confidence: 99%
“…Because bile acids play a key role in lipid and energy homeostasis, alterations in lipid metabolism are inevitable in cholestatic liver diseases [4,5,25]. De Vriese and colleagues reported the results of lipid analysis of BDL rats and identified hypercholesterolemia and changes in the serum phospholipid profile, in proportion to serum levels of total bilirubin and ALP; however, a decrease in liver fat content in BDL rats was also observed [4].…”
Section: Discussionmentioning
confidence: 99%
“…Ligature and common bile duct resection can be used as a model of the alterations of cholesterol metabolism in biliary atresia 28 . Cholestasis increased the serum levels of total cholesterol and triacylglycerides, which is in accordance with the literature 8 .…”
Section: Total Serum Cholesterol and Triacylglycerides Serum Concentrmentioning
confidence: 99%